Audio and linguistic prediction of objective and subjective cognition in older adults: what is the role of different prompts? - Badal, Varsha D.; Tran, Caitlyn; Brown, Haze; Glorioso, Danielle K.; Daly, Rebecca; Molina, Anthony J. A.; Moore, Alison A.; Bilal, Erhan; Lee, Ellen E.; Depp, Colin A. (Frontiers in Psychiatry, 2025)
BackgroundPsycho-linguistic and audio data derived from speech may be useful in screening and monitoring cognitive aging. However, there are gaps in understanding the predictive value of different prompts (e.g., open ended or structured) and the relationship of features to subjective versus objective cognition.ObjectiveTo advance understanding of method variation in speech-analysis based psychometry, we evaluated targeted prompts for classification of impaired cognition and cognitive complaints.MethodA sample of 49 older participants (mean age: 76.9, SD: 8.5) completed short interview questions and cognitive assessments. Acoustic and Linguistic Inquiry through Word Counting i.e., LIWC (verbal content-based) features were derived from answers to open ended questions about aging (AG) and the Cookie Theft task (CT). Outcomes were objective cognitive ability measured using Telephone Interview for Cognitive Status (TICS-m), and subjective cognition using Cognitive Failures Questionnaire (CFQ).ResultsA combined feature set including acoustic and LIWC (verbal content) yielded excellent classification results for both CFQ and TICS-m. The F1, precision and recall for CFQ elevation was 0.83, 0.85 and 0.82, and for TICS-m cutoff was 0.92, 0.92 and 0.92 respectively (using single learners). Features derived from CT task were of greater relevance to TICS-m classification, while the features from the AG task were of greater relevance to the CFQ classification.ConclusionAcoustic and psycholinguistic features are relevant to assessment of cognition and subjective cognitive complaints, with combined features performing best. However, subjective and objective cognitions were predicted to differing extents by the different tasks, and the feature sets.